REPUTABLE VS PREDATORY: HOW TO SPOT THE DIFFERENCE? - Kenzhina, Inesh; Orazymbetova, Zhuldyz (Nazarbayev University Library, 2022)
As part of the information literacy initiatives, the NU Library held an Open IL Session entitled Reputable vs Predatory: How to Spot the Difference? on 7 September 2022, Wednesday, 10:30AM - 12:00PM. This session was in hybrid format to accommodate interested researchers and scholars who wanted to know more about journal publishing. In line with our #WorkshopWednesday, this open IL session aims to: -Explore the difference between reputable and predatory journals; -Identify the various criteria to look out for when submitting manuscripts to a journal; -Understand the value of journal rankings based on Impact Factor, Quartile, etc. This session was conducted by Zhuldyz Orazymbetova, Subject Librarian for GSB and CPS, and Inesh Kenzhina from Clarivate Analytics for this session.
Keywords: journal rankings; Type of access: Open Access; predatory journals; reputable journals